Clonal analysis of the late stages of erythroleukemia induced by two distinct strains of Friend leukemia virus. - Mager, D (1981)
We observed striking differences between the tumorigenic colony-forming cells present in the spleens of mice late after infection with the anemia-inducing strain of Friend leukemia virus (strain FV-A) and those present after infection with the polycythemia-inducing strain (strain FV-P). Cells within primary colonies derived from FV-A- and FV-P-transformed cells (CFU-FV-A and CFU-FV-P, respectively) contained hemoglobin and spectrin, indicating that the CFU-FV-A and CFU-FV-P were transformed erythroid progenitor cells. The proportion of cells containing hemoglobin was relatively high (> 25%) in newly isolated cell lines derived from CFU-FV-P colonies, whereas cell lines derived from CFU-FV-A colonies had only low levels (0 to 2%) of hemoglobin-containing cells. A high proportion of the cell lines derived from CFU-FV-A colonies responded to pure erythropoietin and accumulated spectrin and hemoglobin, whereas the cell lines derived from CFU-FV-P colonies did not. A cytogenetic analysis indicated that primary CFU-FV-P colony cells were diploid, whereas chromosomal aberrations were observed in the immediate progeny of CFU-FV-A. The presence of unique chromosomal markers in the majority of the cells within individual colonies derived from CFU-FV-A suggested that these colonies originated from single cells. Finally, leukemic progenitor cells transformed by strain FV-A appeared to have an extensive capacity to self-renew (i.e., form secondary colonies in methylcellulose), whereas a significant proportion of the corresponding cells transformed by strain FV-P did not. In addition, the self-renewal capacity of both CFU-FV-A and CFU-FV-P increased as the disease progressed. From these observations, we propose a model for the multistage nature of Friend disease; this model involves clonal evolution and expansion from a differentiating population with limited proliferative capacity to a population with a high capacity for self-renewal and proliferation.